Displacement as Precarious Inhabiting: Care and Repair at the Urban Margins - (:unkn) unknown (Springer Nature Switzerland, 2024)
We are all left with a broken world, where there is no way back to integrity. The only choice is to learn to live with the fragments, ‘staying with the trouble’ of displacement, mending holes, restoring functions, in an attempt to preserve some form ...
Keywords: Desplazamiento urbano; Cuidados